Covidence vs Excel for the title and abstract review stage of a systematic review. Issue 4 (December 2016) - Macdonald, M.; Martin Misener, R.; Weeks, L.; Helwig, M.
Abstract : Background: Although spreadsheet formats such as Excel are commonly used to manage the title and abstract review stage of JBI reviews, these formats necessitate considerable data entry and may be labor intensive. Covidence is a software platform owned by Veritas Health Innovation in Victoria, Australia, and it is the platform used for the conduct of Cochrane Systematic Reviews. Currently the platform is accessed by opening an account online free of charge, and account holders are bound by the terms of use of the platform and the platform can be modified or discontinued without notice. Covidence provides a series of functionalities to facilitate the review process including: importing citations from a variety of reference management systems; removing duplicate entries (sensitivity to deduplication not considered to be high); programming the number of reviewers; recording an audit trail on reviewer decisions; decision choices of yes, no or maybe; assigning conflict resolution when reviewers disagree; and title and abstract inclusion/exclusion criteria and key words. A yes or maybe decision results in a full text article review. Objective: To compare the strengths and limitations of Covidence versus Excel for the conduct of a title and abstract review. Methods: Each team member obtained a Covidence account, and the team's Information Scientist conducted the search as outlined in the systematic review protocol search strategy and uploaded titles and abstracts to the Covidence platform for team member review. The team received training on the use of Covidence and trialled its use on 25 articles. The team will meet once during title and abstract review and once following this review to outline the strengths and limitations of Covidence versus Excel. Our team will begin using the platform in approximately two weeks. The period of title and abstract review will occur over one month. The assessment of strengths and limitations of Covidence and Excel will be conducted with reviewers completing a brief questionnaire based on Covidence functionalities, tracking review times, and through a team discussion following title and abstract review. Results: Preliminary assessments were primarily favorable, such as ease of access, page layout of the abstract, and identification of the reviews completed to date as well as those remaining. Covidence limitations will be assessed via the review process. Discussion/Conclusion: Our training experience indicates that Covidence has the potential to greatly facilitate the title and abstract review stage of a JBI systematic review. While the online platform has been available for free, there will be a subscription fee introduced in May, 2016, which may limit the availability of this program for some researchers in the future.